Examination of Purchasing Power Parity Hypothesis: Evidence from Unit Root and Cointegration analysis of dinar-euro and dinar-dollar exchange rates - Petrović, Predrag M (Industrija, 2014)
The paper shows the results of an empirical analysis of the relative variant of purchasing power parity (PPP) for dinar-euro and dinar-dollar exchange rates. The study was conducted for the period January 2007 – August 2013 and involved testing of the empirical foundation of strong and weak PPP forms. The first part of the strong PPP form testing comes down to examination of non-stationarity of dinar-euro and dinar-dollar real exchange rates by use of standard unit root tests (ADF, PP, KPSS, DF-GLS). Considering that the results obtained by different tests differ, the final conclusion about the non-stationarity of the series has been reached on the basis of their correlogram and ordinary and partial autocorrelation functions. Having in mind reduced power and bias of standard unit root tests in the presence of structural breaks, the initial findings have been checked by use of the LS (Lee and Strazicich) unit root test for models A and C with one and two structural breaks. The findings confirm the non-stationarity of the real exchange rates. Testing of the weak PPP form was conducted using Johansen and Engle-Granger cointegration tests in order to examine the presence of a long-run equilibrium relationship between the nominal exchange rates and inflation differentials, i.e. the corresponding price indices. The test results show that the series are not cointegrated. The non-stationarity of the real exchange rates and the lack of cointegration between the series indicate that PPP, regardless of the form, has no empirical support. Such results are no surprise considering that the analysis refers to a relatively short period of time, and having in mind that even the strongest supporters of PPP have acknowledged that PPP is not a short-run relationship.
Keywords: Unit root tests; Nominal exchange rate; Real exchange rate; Purchasing power parity; Cointegration